Sandur Art as an Effort to Internalize Multicultural Education - Arif Hidajad; Hujuala Rika Ayu (Yayasan Keluarga Guru Mandiri, 2025)
The internationalization of education in Indonesia faces challenges such as disparities in quality, inadequate curricula, language barriers, and limited recognition of qualifications. Additionally, managing cultural, ethnic, and linguistic diversity leads to discrimination, inequality of access, and a lack of cultural representation in the curriculum. This study aims to analyze the root causes of multicultural education issues in Indonesia, focusing on Sandur Art as an effort to internalize multicultural values. A historical-descriptive method is used to trace the relationship between perceptions, acceptance, problem-solving attitudes, independence, creativity, and inspiration in promoting multicultural awareness. The research results show that Sandur Art can build a positive perception, acceptance, and problem-solving attitude towards cultural diversity through its rich symbolism and collaborative practices. The values of independence and creativity in Sandur Art also foster the creation of an inclusive educational environment. In conclusion, integrating Sandur Art into education can effectively shape globally competent and inclusive citizens. This study contributes to expanding the understanding of the role of traditional arts in supporting multicultural education in Indonesia.